2006 Sixth European Dependable Computing Conference 2006
DOI: 10.1109/edcc.2006.17
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from the deployment of a high-interaction honeypot

Abstract: This paper presents an experimental study and the lessons learned from the observation of the attackers when logged on a compromised machine. The results are based on a six months period during which a controlled experiment has been run with a high interaction honeypot. We correlate our findings with those obtained with a worldwide distributed system of lowinteraction honeypots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 4 publications
4
45
1
2
Order By: Relevance
“…This allows to evaluate its capability to cope with heterogeneous and diverse samples. We focus this analysis on the first 30 days of operation 3 . This period corresponds in fact to the most interesting one from the point of view of the ScriptGen learning.…”
Section: Scriptgen and Real Attacksmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows to evaluate its capability to cope with heterogeneous and diverse samples. We focus this analysis on the first 30 days of operation 3 . This period corresponds in fact to the most interesting one from the point of view of the ScriptGen learning.…”
Section: Scriptgen and Real Attacksmentioning
confidence: 99%
“…Also, recent work has shown the usefulness of gathering experimental data to model and better understand the threats due to attackers [24,29]. Alata et al have shown the merits of using honeypots for the statistical modeling of attack processes [20,2] and, more specifically, the merits of high interaction ones [3]. The benefits due to high interaction honeypots, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Quite simply a high interaction honeypot can be any vulnerable system that is connected to a network and can be monitored for analysis. Authors in [5] describe these as truly vulnerable systems that can be probed, attacked and exploited, once the attacker gains access to the system the honeypot can be used in a botnet or to carry out other attacks. This gives light to some ethical issues with regard to continuing the research once a honeypot has been compromised, when should the system be taken back from the attacker and should it really be used in the type of attacks that it has been designed to prevent?…”
Section: Introductionmentioning
confidence: 99%
“…In the context of this work, a harvesting attack is a mass exploitation where an attacker initiates communications with multiple hosts in order to control and reconfigure them. This type of automated exploitation is commonly associated with worms, however, modern bot software often includes automated buffer-overflow and password exploitation attacks against local networks 1 . In contrast, in a scanning attack, the attacker's communication with multiple hosts is an attempt to determine what services they are running; i.e., the intent is reconnaissance.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, a single host, whether scanning This work was done while the author was affiliated with the CERT/NetSA group at the Software Engineering Institute, Carnegie Mellon University. 1 A representative example of this class of bot is the Gaobot family, which uses a variety of propagation methods including network shares, buffer overflows and password lists. A full description is available at http://www.trendmicro.com/vinfo/ virusencyclo/default5.asp?VName=WORM AGOBOT.GEN.…”
Section: Introductionmentioning
confidence: 99%